Urgency Pengelolaan Potensi Bahari Berdasarkan Undang- Undang Nomer 27 Tahun 2007 Tentang Pengelolaan Wilayah Pesisir Dan Pulau-Pulau Kecil - Muhamad Ikbal; Arif Yumanrdi; Tito Wahyono; Rosidin; Dhian Tyas Untari (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2021)
Indonesia's maritime potential is very large and its utilization must be as much as possible to provide a positive impact for the community as mandated in the 1945 Constitution. This study is a conceptual study that aims to describe the urgency of marine potential management based on Law No. 27 2007 on the Management of Coastal and Island Areas. -small island. Secondary data sources become material in the study. The results of the study are expected to be preliminary research for further researchers in optimizing the marine potential in Indonesia. Maritime sovereignty cannot be achieved only with the efforts of one or two parties, but requires coordination between all stakeholders.